RODENTIA IN THE AMU DARYA DELTA (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The article presents data on the registered species of Rodentia in the reserve zone of the Amu Darya Delta, especially the development of rodent (Rodentia) natural habitats, changes in the irrigation system and other construction services, comprehensive re-examination of this genus and re-evaluation of its significance.